QuickStart radiotherapy: an inter-professional approach to expedite radiotherapy treatment in early breast cancer. Issue 3 (20th May 2015) - Lee, Grace; Dinniwell, Robert E.; Purdie, Thomas G.; Rahman, Mohammad; Foxcroft, Sophie; Fyles, Anthony
Abstract Background and purpose This study aims to develop an expedited radiotherapy (RT) process and evaluate its time savings in women requiring whole breast RT. Material and methods An inter-professional RT team streamlined the computed tomography (CT) simulation and treatment pathway for a 'QuickStart' process. Target delineation was performed by an advanced practice radiation therapist and approved by the radiation oncologist (RO) for planning. Automated breast planning software was used for treatment planning and standard quality checks were performed. To assess time savings, the initial 25 QuickStart patients were matched with women who underwent whole breast simulation on the same day (±3 days), treated using the conventional process. Results A total of 73 post-lumpectomy women were treated through the QuickStart process; the median consent-to-RT was 2 days (range: 0–13) and the mean CT simulation-to-RT treatment was 2 hours and 42 minutes (SD 0:30). In the subgroup analysis, QuickStart patients saved an average of 11 days from CT simulation-to-RT and had shorter median wait-times for both surgery/chemotherapy-to-RT (60 versus 38 days; p=0·002) and consultation-to-RT (7 versus 20 days; p<0·001). Conclusions Through inter-professional team efforts and the application of automated planning software, we have achieved a process that significantly decreases patient wait-times while maintaining the quality of whole breast RT.